ERP Training Evaluation: A state-wide system implementation in Brazil - Menezes da Costa Neto, Arlindo; Bomfim Gomes Dias, Hellen; Branco de Holanda, Victor (Revista de Contabilidade da UFBA, 2023)
The work presented here aims to develop a new methodology to evaluate adherence to an ERP training strategy. We derive our method from the observations from the GRP implementation in Rio Grande do Norte state, Brazil. Our methodology proposal derives from how Event Studies measure the abnormal return of an event within a data metric. In our study, the event is the training provided to employers on using the ERP, while the “return” data is the measured system input made by users who received that training. In our understanding, the training procedures are necessary to ensure the correct usage of an ERP. This understanding of how proper planning may be helpful and cost-effective allows us to claim our main contribution. We expect this methodology and experience may allow ERP trainers to design the appropriate training protocol for the trained group and expected ERP usage.